Microsurgical excision of intracranial epidermoids: a short surgical series of 12 cases - Godugu, Bhaskar; Ambarapu, Mastan Reddy; Akyam, Lakshman Rao; Maila, Sharath Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Intracranial epidermoids are rare congenital cystic lesions where total excision is often difficult resulting in recurrence. In the current series we tried to analyze and report, the clinical findings, imaging criteria for diagnosis, surgical management strategy to achieve radical resection and outcomes were studied prospectively. Here we report our short experience with intracranial epidermoids as a whole. Methods: 12 cases of intracranial epidermoids confirmed radiologically between Feb 2009 and Dec 2013 were operated by different surgical approaches according to the location of the lesion by micro neurosurgical techniques to achieve total resection. All these patients were followed up for various periods and results analyzed. Results: Of the 12 epidermoids 5 were in CP angle, 4 were in supratentorial location. Of these 2 patients died and Transient facial palsy was observed in two cases and lower cranial nerve palsy in another case which improved later. 2 patients required VP shunt and there were no recurrences in the series. Total resection of the lesion was achieved in majority of the patients (83.3%) by microsurgical techniques. Conclusions: With the availability of good imaging techniques and modern micro neurosurgical techniques it is possible to achieve total or near total excision where ever possible to avoid recurrence of the lesions, resulting in total cure of the patient.